Cognitive impairment and depressive symptoms coexisting in an elderly man - Masiran, Ruziana; Tze, Nicholas Ping Pang (BMJ Publishing Group, 2017)
We report a case of a man aged 67 years presenting with recent depressive symptoms and paranoid ideations in addition to 1-year cognitive impairment. He has vascular risk factors and family history of memory loss. An episode of depression 2 decades ago resolved spontaneously but was followed by occupational decline. On mental state examination, he denied having depressed mood, hallucinations or delusions, but there were prominent word-finding difficulties and impaired attention and concentration.